2017
DOI: 10.1080/02813432.2017.1288692
|View full text |Cite
|
Sign up to set email alerts
|

How the probability of presentation to a primary care clinician correlates with cancer survival rates: a European survey using vignettes

Abstract: ObjectiveEuropean cancer survival rates vary widely. System factors, including whether or not primary care physicians (PCPs) are gatekeepers, may account for some of these differences. This study explores where patients who may have cancer are likely to present for medical care in different European countries, and how probability of presentation to a primary care clinician correlates with cancer survival rates.DesignSeventy-eight PCPs in a range of European countries assessed four vignettes representing patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…40,41 This suggests that, at least in the UK, delayed diagnosis of cancer is not caused solely by gatekeeping, but by other healthcare system factors, patient behaviour, and healthcare provider factors. 15,[42][43][44][45][46] Implications for policy and research Caution should be exercised in interpreting these findings to the policy context. Policymakers eager to reduce costs and use may conclude that reduction in specialist healthcare use and expenditure makes gatekeeping a favourable system.…”
Section: Discuss This Articlementioning
confidence: 99%
“…40,41 This suggests that, at least in the UK, delayed diagnosis of cancer is not caused solely by gatekeeping, but by other healthcare system factors, patient behaviour, and healthcare provider factors. 15,[42][43][44][45][46] Implications for policy and research Caution should be exercised in interpreting these findings to the policy context. Policymakers eager to reduce costs and use may conclude that reduction in specialist healthcare use and expenditure makes gatekeeping a favourable system.…”
Section: Discuss This Articlementioning
confidence: 99%
“… 21 However, there are wide variations in the degree of gatekeeping between countries, with no simple binary model as to whether or not a country has a ‘GP-as-gatekeeper’ system, and a European study found no link between a higher probability of initial consultation with a GP and poorer cancer survival. 22 …”
Section: Introductionmentioning
confidence: 99%
“… 59 However, there are important variations in the level of gatekeeping between countries, with no simple binary model as to whether or not a country has a ‘GP-as-gatekeeper’ system, and a European study found no association between cancer survival and a probability of presentation to a GP. 36 …”
Section: Discussionmentioning
confidence: 99%
“…More information about this process is given elsewhere. 36 No changes to the demographic questions were made. One of the vignettes No changes to the questions were made following this second pilot.…”
Section: Development Of the Questionnairementioning
confidence: 99%